Drivers of Entrepreneurship and Post-Entry Performance of Newborn Firms in Developing Countries - Francesco Quatraro; Marco Vivarelli (Institute for the Study of Labor (IZA), 2013)
The aim of this paper is to provide an updated survey of the state of the art in entrepreneurial studies, with a particular focus on developing countries (DCs). In particular, the same concept of entrepreneurship will be critically discussed, then moving to the institutional, macroeconomic and microeconomic conditions affecting the entry of new firms and the post-entry performance of newborn firms.
Keywords: L26; O12; 330; entrepreneurship; new firm; innovation; development